2020
DOI: 10.1055/s-0040-1717078
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of New Monoclonal PF4-Specific Antibodies as Useful Tools for Studies on Typical and Autoimmune Heparin-Induced Thrombocytopenia

Abstract: Background Heparin-induced thrombocytopenia (HIT) is typically caused by platelet-activating immunoglobulin G (IgG) antibodies (Abs) against platelet factor 4 (PF4) complexed with heparin (H). Much less frequent “autoimmune” HIT is distinguished from typical HIT by platelet activation without heparin and the presence of both anti-PF4/H and anti-PF4 IgG. We developed three murine monoclonal anti-PF4 Abs with a human Fc-part, 1E12, 1C12, and 2E1, resembling autoimmune HIT Abs. Objectives To characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 28 publications
3
48
0
Order By: Relevance
“…Our results explain why some VITT samples tested in studies by Schultz et al 2 and Greinacher et al 1 were inhibited by therapeutic doses of heparin. Our findings suggest VITT antibodies cause platelet activation through a similar heparin-like mechanism by stabilizing complexes of PF4, aligning the Fc-portion in close proximity and crosslinking FcγRIIa receptors on platelets, similar to that of the monoclonal antibody, 1E12, which can activate platelets independent of heparin 15 .…”
Section: Binding Site Of Vitt Antibodies On Pf4mentioning
confidence: 61%
See 2 more Smart Citations
“…Our results explain why some VITT samples tested in studies by Schultz et al 2 and Greinacher et al 1 were inhibited by therapeutic doses of heparin. Our findings suggest VITT antibodies cause platelet activation through a similar heparin-like mechanism by stabilizing complexes of PF4, aligning the Fc-portion in close proximity and crosslinking FcγRIIa receptors on platelets, similar to that of the monoclonal antibody, 1E12, which can activate platelets independent of heparin 15 .…”
Section: Binding Site Of Vitt Antibodies On Pf4mentioning
confidence: 61%
“…Monoclonal antibodies against PF4, such as KKO 18 and 1E12 15 facilitate the formation of ultra-large complexes of PF4 on the platelet surface. Previous studies using antibodies from HIT patients 19 and monoclonal antibodies that resemble HIT antibodies 15 have demonstrated that the higher affinity of HI antibodies in some HIT patients can cluster PF4 tetramers and create platelet-activating immune complexes, in the absence of heparin.…”
Section: A C C E L E R a T E D A R T I C L E P R E V I E Wmentioning
confidence: 99%
See 1 more Smart Citation
“…HIT is caused by platelet-activating immunoglobulin G (IgG) antibodies against platelet factor 4 (PF4) complexed with heparin. This complex then binds to the platelet FcRγIIA receptors and causes platelet activation and formation of platelet microparticles [ 39 ]. These microparticles initiate the formation of blood clots and inducing a prothrombotic cascade, which consequently decreases platelet count and causes thrombocytopenia.…”
Section: Resultsmentioning
confidence: 99%
“…In the study by Vayne et al in this issue of Thrombosis and Haemostasis, 12 humanized monoclonal antibodies (humAbs) were raised against a complex of CXCL4 with heparin to serve as a model for the antibodies found in patients with autoimmune HIT. Since these antibodies contained a human Fc region, they behaved as HIT or autoimmune HIT antibodies, similar to those found in patients.…”
mentioning
confidence: 99%